IMPLEMENTASI ANGGARAN CSR PADA BANK SYARIAH - Muhammad Adil; Idrawahyuni .; Muhammad Nur Abadi; Muhammad Nasrun (Universitas Muhammadiyah Luwuk Banggai, 2020)
This study aims to determine how much the budget and form of CSR implementation at Bank Syariah Mandiri for the community and the surrounding environment. This study uses a method with a descriptive approach. The case study method is an empirical inquiry that investigates phenomena in the context of real life, where the boundaries between phenomena and contexts are not clearly visible. Case studies are limited to quantitative evidence. The data used in this study are secondary data on the Budget Realization Report and CSR implementation in 2012-2015. The data is a documentation of the Annual Report on Budget Realization and the implementation of BSM Bank CSR 2012-2015. The analysis technique used in this research is quantitative descriptive method. Descriptive refers to the transformation of raw data into a form that will make it easier for readers to understand and interpret the meaning of the data or numbers displayed. The steps taken in analyzing this data include: 1. Calculating the implementation of Bank Syariah Mandiri's 2012-2015 CSR budget by distributing a maximum of 2% of profit after tax. 2. calculate the ratio of realization of BSM's CSR budget since 2012-2015. 3. Describe the data from the calculation of the budget implementation ratio.From this research, it is found that the Bank distributes zakat funds for companies, employees, customers, and the general public to those who are entitled by synergizing with LAZNAS BSM through an efficient and beneficial program for the community. This CSR activity will provide added value and positive value to society both as customers and the general public. In another position, the Bank's Corporate Image will get better so that this will increase public confidence in the existence of BSM and also all of the Bank's business products.